Custos e sua associação com a operação logística de empresas varejistas de E-COMMERCE - Cerresi, Luis Carlos (2019)
The advance of Internet use directed retailers to offer products through a new sales channel, the virtual one. This fact made the consumers become more alert in the process of post purchase, since they have the expectation of receiving their purchases correctly and within the agreed term. Thus, companies in this sector need to find ways of structuring and managing costs in areas that were previously not as customer-related as logistic operations. Despite the relevance of logistics, most companies decide to outsource various activities in this area, such as transportation, in order to reduce costs. Even considering the fact that costs are a theme mentioned in the research on the logistics operation, there is still a gap about the elements that compose it, especially in the e-commerce sector, and precisely because of this, the general objective of this study was, through a basic exploratory qualitative research, to investigate how the costs are associated with the logistics operation, specifically in the activity of transport in retail companies of the Brazilian electronic commerce. The review of the literature on these themes, together with the results from the data collected in the field, led to the development of a theoretical-empirical model that showed not only the strong association between the cost construction in logistics (its importance, role, reason) e-commerce, but also the elements that make up such a relationship. In this way this research brought several theoretical and managerial contributions, as well as suggestions for future researchers interested in studying these topics